Perspectives of Adolescents and Young Adults With Inflammatory Bowel Disease on a Biopsychosocial Transition Intervention: Qualitative Interview Study - Brooke Allemang; Ashleigh Miatello; Mira Browne; Melanie Barwick; Pranshu Maini; Joshua Eszczuk; Chetan Pandit; Tandeep Sadhra; Laura Forhan; Natasha Bollegala; Nancy Fu; Kate Lee; et al. (JMIR Pediatrics and Parenting)
Abstract BackgroundThe transition from pediatric to adult health care marks a complex and pivotal process for adolescents and young adults with inflammatory bowel disease (IBD). This group requires support regarding disease self-management, skill development, and system navigation in preparation for transition. Evidence-based interventions are needed to promote optimal health and psychosocial outcomes for adolescents and young adults with IBD during this period. ObjectiveA qualitative study embedded within a randomized controlled trial was conducted to evaluate the perceived impact of a biopsychosocial transition intervention on the transition experiences of adolescents and young adults, their views on the intervention, and recommendations for future care. MethodsThis patient-oriented research study used a qualitative descriptive design. Virtual semistructured interviews were held with 21 adolescents and young adults with IBD (16‐18 y) enrolled in the randomized controlled trial (intervention arm n=11 and control arm n=10). Interviews were audio-recorded, transcribed, and analyzed using an inductive approach to reflexive thematic analysis. Five members of a Youth Advisory Panel with lived experience of IBD collaborated throughout data analysis, interpretation, and the presentation of findings. ResultsWe constructed three themes through our analysis: (1) making meaning of transitions in care; (2) perceptions and impact of the biopsychosocial transition intervention; and (3) considerations for future transition care, including the importance of individualized support. ConclusionsOur findings illustrate the importance of relationships and the impact of a biopsychosocial intervention on adolescents’ and young adults’ confidence, knowledge, and self-management skills during transition. The results, which indicate the criticality of tailoring transition supports according to adolescents’ and young adults’ preferences and characteristics, will be used to refine the biopsychosocial intervention before it can be scaled and spread.